PENGARUH FAMILY INVOLVEMENT TERHADAP TAX AGGRESSIVENESS DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - DEWI, CITRA; PRASTIWI, DEWI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of family involvement on tax aggressiveness with the audit committee as a moderating variable. The sample used in this study was 44 samples of family companies listed on the Indonesia Stock Exchange 2014-2017. This study using SPSS 22 for processing data and purposive sampling for sample determination. The results of this study indicate that family involvement in the board of commissioners and directors will reduce the level of corporate tax aggressiveness. This is indicated by the increase in the CETR number when there is a large family involvement in the company. The researcher also uses audit committee variables as moderating variables measured using four proxies processed by PCA whose purpose is to summarize the four variables into new variables, the results of Moderated Regression Analysis indicate that the audit committee has not been able to strengthen or weaken the relationship of family involvement on tax aggressivenessKeywords: Family involvement, , tax aggressiveness, audit committee